Muscle strength and functional outcome after prone positioning in COVID-19 ICU survivors. (April 2022) - Binda, Filippo; Rossi, Veronica; Gambazza, Simone; Privitera, Emilia; Galazzi, Alessandro; Marelli, Federica; Santambrogio, Martina; Adamini, Ileana; Grasselli, Giacomo; Laquintana, Dario
Abstract: Objective: To evaluate the muscle strength and functional level of patients discharged from intensive care unit (ICU) in relation to the swimmer position as a nurse intervention during pronation. Methods: Prospective study conducted in the hub COVID-19 center in Milan (Italy), between March and June 2020. All patients with COVID-19 discharged alive from ICU who received invasive mechanical ventilation were included. Forward continuation ratio model was fitted to explore the statistical association between muscle strength grades and body positioning during ICU stay. Results: Over the 128 patients admitted to ICU, 87 patients were discharged alive from ICU, with available follow-up measures at hospital discharge. Thirty-four patients (39.1%) were treated with prone positioning as rescue therapy, for a total of 106 pronation cycles with a median duration of 72 (IQR 60–83) hours. Prone positioning did not influence the odds of showing particular level of muscle strength, in any of the evaluated districts, namely shoulder (OR 1.34, 95%CI:0.61–2.97), elbow (OR 1.10, 95%CI:0.45–2.68) and wrist (OR 0.97, 95%CI:0.58–1.63). Only in the shoulder district, age showed evidence of association with strength (OR 1.06, 95%CI:1.02–1.10), affecting people as they get older. No significant sequalae related to swimmer position were reported by physiotherapists or nurses. Conclusion: Swimmer position adopted during prone ventilation is not associated with worse upper limb strength or poor mobility level in COVID-19 survivors after hospital discharge.